Mapping practices of Christian education: Toward a framework of contextual differences around the globe. (March 2017) - de Muynck, Bram; Reijnoudt-Klein, Willemieke; Spruyt-de Kloe, Marike
This article reports the development of a framework that structures differences in Christian educational practices worldwide. One of its purposes is to simplify the complexity of the contexts in which global partners cooperate. The framework also offers the theoretical basis for an instrument that nongovernmental organizations can use to determine how to choose the appropriate support for Christian education in a certain region. Based on a literature search and a validation study in Zambia, we find three overarching domains in which 24 dimensions are identified: the teaching and learning processes in classrooms; the educational administration, including stakeholders and their motives, aims and ideals to maintain Christian education; and four kinds of societal factors (historical and cultural, religious, legal and political, and socioeconomic). The framework will be the basis for empirical validation studies in different regions. An operational instrument for determining support needs is currently being developed.